The Structure of Classroom Talk: Applying the Sinclair & Coulthard Model in Teaching Descriptive Text - Ami Girsang; M. Rafif Zaki Ramadhan; Rina Trie Syahputri; Sandra Sridevi Hutapea; Zuraima Fitriani Salim (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to explore the use of classroom talk in Indonesian EFL classrooms, specifically when teaching descriptive texts. Utilizing Sinclair & Coulthard's (1975) discourse analysis theory, the study focuses on the Initiation-Response-Feedback (IRF) model, which offers a framework for analyzing classroom interactions. By applying this model, classroom discourse can be broken down into a hierarchical structure that includes Exchanges, Moves, and Acts. This structure allows for a detailed examination of teacher-student communication, making its subtle nuances more explicit and accessible for analysis. The IRF model is widely recognized for its applicability and effectiveness in identifying the functional roles of utterances in classroom talk. One key observation from this study is that teacher-led initiation and questioning often dominate the discourse, with students primarily responding to the teacher’s prompts. The study suggests that the implications of the IRF model can help teachers reflect on their communication patterns and improve their teaching methods. By transforming teacher-centered scaffolding into a more student-centered approach, teachers can foster more effective interactions that enhance student engagement and learning. The study also highlights the importance of using the IRF model as a diagnostic tool for improving classroom communication practices and encouraging more dynamic and student-oriented teaching methods.